Upaya Hukum Terhadap Wanprestasi dalam Perjanjian Pengiriman Barang di PT. on Time Express Kantor Cabang Bali - Dewa Putu Adi Putra; I Nyoman Budiana (Fakultas Hukum, Universitas Warmadewa, 2022)
On Time Express is a foreign investment company engaged in land, sea and air transportation services. Also called financing companies for goods delivery services, namely business entities outside banks and non-bank financial institutions that are specifically for carrying out economic activities in delivering goods and services. The work contract system is implemented based on the principle of trust as a service provider, a standard agreement is written based on the principle of freedom of employment contract made by PT. OnTime Express. That is, both parties, both service providers and consumers, together and agree to make a work contract agreement. But in reality, the work contract agreement as a service provider in its operations is not uncommon for problems that arise due to unexpected results between the parties. The consumer is unable to fulfill the contents of the agreement as agreed in the initial agreement resulting in a breach of contract. This must be resolved to maintain a good relationship and balance between rights and obligations according to the mutually agreed agreement. The purpose of this paper is to provide accountability for consumers and understanding in resolving violations of employment contract issues. This paper was written using empirical methods and data analysis techniques that are descriptive analytical. Based on research on the contract of delivery of goods, there are still many contract violations in PT. On Time Express by consumers. Most of the breaches of contract issues are resolved by non-litigation methods, which are negotiation and mediation.